Code Mixing in The Computer Classroom Interaction - Ika Swantika; Refin Harissandi; Rossya Diva Anwar (ELT (English Language Teaching Prima Journal), 2023)
The aims of this study are to find out the type of code-mixing used by the teacher and students and the factors causing the teacher and students mix the language in computer classroom interaction. Code mixing is the combining of two or more languages or more language varieties in speech. The teacher and students used Code mixing to avoid misunderstanding when they had conversation in the class. Descriptive qualitative design was conducted in this study. The subjects of this study are the teacher and students from the Teknologi Informatika STMIK Pelita Nusantara Medan. The data were collected by doing observation and recording the teacher and students’ utterances in classroom interaction. From the research, it was found the type of code-mixing used by the teacher and students were inner code mixing and outer code mixing. The factors causing teacher did the code-mixing were factors of limited use of codes, factors of function and purpose, and factors of habits. According to the percentages of the questionnaire result the data shows that out of 20 students 50% of them chose factors limited use of codes as their reason did the code mixing, 2% chose factors of function and purpose, and 48% chose factors of habits.